PROFIL PERMASALAHAN PESERTA DIDIK YANG MENGALAMI KETIDAKTUNTASAN DALAM BELAJAR (Studi terhadap Peserta Didik di SMP Negeri 2 Batang Kapas) - Suardi, Don Toni; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
Problems studied by the phenomenon and interviews in the field , namely the problem of students who have not completed the study. The purpose of the study described: 1) the personal problems of learners who have not completed the study. 2) The problem of social learners who have not completed the study. 3) The problems of learners who have not completed the study. This research is a quantitative study using descriptive methods. The study population was all students of SMP N 2 Batang Kapas . The techniques used in sampling is the total sampling , samples are taken by students who have not completed the value in learning as much as 53 people. Sources of data in this study is primary data and secondary data. The instrument used in this study is a questionnaire , while the use of data analysis techniques for percentages .Results of research conducted on students who experience problems in learning ketidaktuntasan in SMP N 2 Batang Kapas, the general problem of students who have not completed the study are the criteria a bit. The results based on subvariabel namely: 1) the personal problems of learners who have not completed the study in the category a bit. 2) Social Issues learners who have not completed the study in the category sukup lot. 3) Problems of learners who have not completed the study are in the category of pretty much